Preying on commercial fisheries and accumulating paralytic shellfish toxins: a dietary analysis of invasive dosidicus gigas (cephalopoda ommastrephidae) stranded in pacific Canada - Braid, H.E.; Deeds, J.; DeGrasse, S.L.; Wilson, J.J.; Osborne, J.; Hanner, R.H. (2012)
In fall of 2009, several mass strandings of Humboldt squid (Dosidicus gigas) occurred on Vancouver Island (49 degrees 7' 60N 125 degrees 54'0W). Morphological dissections coupled with DNA barcoding of stomach contents revealed Sardinops sagax (Pacific sardine) and Clupea pallasii (Pacific herring) as their primary prey. Plastic nurdles, fishing line, bull kelp, eelgrass, and a guillemot feather were also discovered. The primary prey, Pacific sardines and Pacific herring, are known to bioaccumulate paralytic shellfish toxins (PSTs); additionally, both PSTs and domoic acid (DA) have been implicated in other mass strandings. Therefore, stomach contents, and other tissues when possible, were tested for PSTs and DA. Testing revealed DA concentrations below regulatory guidance levels for human consumption, yet PSTs were well in excess. Though we cannot conclude that PSTs were the definitive cause of the strandings, our findings are the first report of PSTs in D. gigas.